STUDENTS’ PERSPECTIVES AND CHALLENGES IN ENGLISH SPEECH PROGRAM - Miftahul Jannah; Bustami Usman; Saiful Marhaban (Universitas Syiah Kuala, 2020)
The purpose of this mixed method research is to describe the students’ perspectives, the students’ challenges and how they overcome those challenges in English speech program. Approximately 68 students filled the questionnaires and 15 of them were selected for the interview. The instruments used in this study were a closed ended questionnaire consisting of 22 questions adapted from the public speaking competence rubric proposed by Schreiber, Paul and Shibley (2012) and the interview guideline adapted from Abubakar, Atmowardoyo and Korompot (2017). The findings of the study revealed that the English speech program was an essential program to increase the students’ speaking ability (65%). Moreover, the program gave advantages to the students (51%). It also found out that the program mostly challenged the students to choose the appropriate topic to the audience (69%) and to use good language (59%). From the interview, it found out that the students made the following efforts to overcome the challenges, namely making independent preparation for the performance, doing practice with friends and having consultation with classroom coordinators.